Digital Leadership, Culture & Employee Capabilities: Sustainable Organizational Performance in Education - A Case Study - Retnowati, Catarina Nur; Santosa, Budi (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
In the rapidly advancing technological era, the integration of technology in education becomes crucial. However, research conducted by Askal (2015) reveals a gap between the school's culture and leadership style with the digital era. The study found that 93% of school principals acknowledge the importance of digital leadership, indicating awareness of the need to adapt to digital leadership in this era. Digital leadership, digital culture, and employees' digital capabilities influence the sustainability of organizational performance, particularly in the education sector. Therefore, this research aims to examine the impact of digital leadership, digital culture, and employees' digital capabilities on the sustainability of organizational performance, especially in educational organizations. The study employs survey and structural analysis methods, with a case study conducted at MPK KAJ Middle Schools in South Jakarta and South Tangerang. The results show a significant positive influence between digital leadership and digital culture, digital leadership and employees' digital capabilities, digital culture and organizational performance sustainability, employees' digital capabilities and organizational performance sustainability, as well as between digital leadership and organizational performance sustainability, with digital leadership and digital culture as factors influencing the sustainability of the school's organizational performance through digital leadership.